Leaving the placenta in situ versus conservative and radical surgery in the treatment of placenta accreta spectrum disorders. Issue 3 (18th September 2017) - Kutuk, Mehmet S.; Ak, Mehmet; Ozgun, Mahmut T.
Abstract: Objective: To compare different treatment methods in the management of placenta accreta spectrum (PAS) disorders. Methods: In a retrospective cohort study, medical records were retrieved for patients who underwent elective surgery at 24 weeks of pregnancy or more after a diagnosis of PAS disorder (creta, increta, or percreta) at a center in Turkey between May 2, 2010, and August 10, 2016. The final analysis included patients whose diagnosis was confirmed intraoperatively and for whom complete data were available. Patients were divided into three groups: group 1 included those who underwent hysterectomy without placental removal, group 2 included patients whose placenta was left in situ, and group 3 included those who underwent placental removal and conservative surgery. Results: Among 79 included patients (33 creta, 18 increta, 28 percreta), 27 (34%) were in group 1, 15 (19%) in group 2, and 37 (47%) in group 3. Total blood loss and the amounts of blood products transfused were lowest in group 2; significant differences between groups were noted (all P ≤ 0.001). Surgical complication rates were similar between groups (4/27 [15%], 1/15 [7%], and 11/37 [30%], respectively; P= 0.119). Overall uterine preservation rates were not significantly different between groups 2 and 3 (14/15 [93%] vs 33/37 [89%]; P> 0.99). Conclusion: Leaving the placenta in situ could become the treatment of choice for PAS disorders. Abstract : Leaving the placenta in situ has better outcomes than do radical and other conservative surgical approaches with regard to blood loss and transfusion requirement.